(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Amin M, Harlyan LI, Achmad K, Diantari R. 2022. Profiling the natural settlement habitat of spiny lobster, Panulirus spp. to determine potential diets and rearing conditions in a lobster hatchery. Biodiversitas 23: 2893-2898. The high demand for spiny lobster seeds has triggered research on seed production in a hatchery system. However, the remaining challenges are still in determining suitable live diets and environmental conditions at the early life stages. Thus, the present study investigated the natural settlement habitat of lobster larvae as basic information for developing diets and rearing conditions in an indoor system. One of the most common natural settlement habitats for lobster larvae in Indonesia, indicated by the high catching rates, Gerupuk Bay located in West-Nusa Tenggara, was selected as a studied area. Physicochemical and biological parameters were investigated to obtain the habitat profiles. The results showed that Gerupuk Bay was 18-30 m water depth, 5-6 m transparency, a sandy, and rocky bottom, 27-31oC temperature, 0.1-0.2 m.s-1 current, 5-6 mg/L dissolved oxygen, <0.01 mg/L nitrate, 0.4-0.6 mg/m3 chlorophyll concentration, and salinity of 30-34 practical salinity unit (psu). Furthermore, the present study found at least 16 zooplankton species and 25 phytoplankton species at 0-5 m water depth. The most dominant species on the surface were Echinocamptus hiemalis elongates (90 indi./L), Tortanus derjugini (20 ind./L) at 2.5 m and Oithona sp. with 46 ind./L at 5 m depth. While the most dominant phytoplankton was Oscillatoria sp. (9 ind./L) followed by Rhizosolenia sp. (4 ind./L) at 2.5 m depth, and Favella ehrenbergii (13 ind./L).